2020
DOI: 10.1097/sla.0000000000003800
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Permanent Hypoparathyroidism After Total Thyroidectomy for Benign Disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 30 publications
2
58
1
Order By: Relevance
“…Permanent hypocalcemia occurred in 20.7% of patients in this study which fits within the previously reported frequencies in other studies (0.6% - 21.7%) ( 1 , 10 , 11 , 23 – 25 ). In adults the incidence is lower compared to children (1.0% -12.5%) ( 26 28 ). In our cohort permanent hypocalcemia only occurred in patients who underwent a total thyroidectomy plus lymph node dissection because of thyroid cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Permanent hypocalcemia occurred in 20.7% of patients in this study which fits within the previously reported frequencies in other studies (0.6% - 21.7%) ( 1 , 10 , 11 , 23 – 25 ). In adults the incidence is lower compared to children (1.0% -12.5%) ( 26 28 ). In our cohort permanent hypocalcemia only occurred in patients who underwent a total thyroidectomy plus lymph node dissection because of thyroid cancer.…”
Section: Discussionmentioning
confidence: 98%
“…The risk of POSH after thyroid surgery is influenced by several operative factors. High surgical volume ( 3 , 4 ), routine parathyroid identification and in situ preservation of parathyroid glands ( 5 ) are all reducing the risk of POSH. In contrast, longer operations, reoperation for bleeding, the need for associated central compartment lymph node dissection and the routine use of parathyroid autotransplantation ( 6 ) increase the risk of POSH.…”
Section: Causes Of Postsurgical Hypoparathyroidism (Hypopt)mentioning
confidence: 99%
“…In a multivariable analysis, there was a higher risk of POSH among women, patients over the age of 60 years, patients who underwent parathyroid autotransplantation and those operated in centers with a volume of <100 thyroidectomies per year. Surgeons might not be aware of most of these cases as their self-reported data from the quality register only identified 178 of these 938 patients with POSH ( 4 ).…”
Section: Epidemiology Of Postsurgical Hypoptmentioning
confidence: 99%
“…Hypocalcemia after thyroidectomy is an effect of hypoparathyroidism occurring due to direct injury, devascularization, inadvertent excision of parathyroid glands, or mineral depletion of the bone caused by an increased metabolism [ 8 , 9 ]. Besides female sex, higher age, Graves’ disease and parathyroid gland reimplantation, vitamin D deficiency has been found to be an independent indicator of transient post-operative hypocalcemia following thyroid surgery [ 4 , 8 , 10 12 ]. However, there is no clear cut-off value for vitamin D, and opinions diverge on to what extent vitamin D levels may predict post-operative hypocalcemia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%